(untitled) (MIST International Journal of Science and Technology, 2020)
With technological advancement on the rise, manual crushing of bricks is gradually being replaced by machine crushing to obtain coarse aggregates for construction. However, properties of the brick aggregates obtained from these two methods vary which in turn, may affect the properties of the concrete matrix as well. This study represents a comparison between the machine crushed and manually crushed brick aggregates to be used as coarse aggregates in preparation of concrete. Four types of bricks, namely first class, second class, picket (over burnt) and ceramic were investigated, and each was crushed both manually and mechanically to a usable form of aggregates. The physical and mechanical properties of the brick aggregates derived from the two methods were tested and compared. In all types of brick, aggregates size, shape and strength properties such as flakiness and elongation indices, aggregate impact and crushing values and Los Angeles abrasion value showed lower values for manually crushed aggregate indicating better properties compare to machine crushed aggregates. This was evident while comparing compressive and tensile strength of concrete prepared with both manually and machine crushed first class and picket brick aggregates. Concrete with manually crushed brick aggregates showed marginally higher compressive and tensile strength in both types of brick aggregates. MIJST, Vol. 8(1), June 2020: 1-9